GURU PROFESIONAL ADALAH KUNCI MEWUJUDKAN PENDIDIKAN BERKUALITAS - Nana Sepriyanti (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
The keyword to achieve quality education is depend on profesional teacher in their fields, therefore there should be a concrete step in an effort to lift the image of the teacher profession as an honorable profession, so that teachers can work as much as possible in building a quality education. Professional responsibility of teachers is not fragmentary, but with entirely, completely, as much as possible from upstream to downstream. All thing are not only teacher responsibility of the students or schools, but will be fully responsible to Allah SWT.